Importance of the Complement Alternative Pathway in Serum Chemotactic Activity During Sepsis. Issue 4 (October 2018) - Xu, Ganqiong; Feng, Yan; Li, Dan; Zhou, Qichang; Chao, Wei; Zou, Lin
Abstract : ABSTRACT: Serum chemotactic activity is important in regulating neutrophil migration. The ability of neutrophils to migrate to infectious site is crucial for host effective pathogen control, but unregulated neutrophil activation can also cause tissue damage. During bacterial sepsis, the complement alternative pathway (AP) is massively activated in blood and tissues and reportedly contributes to sepsis pathogenesis. Complement factor B (FB) is an essential component of the AP activation. However, the impact of FB/AP activation on blood chemotactic activity during bacterial infection is unclear. In this study, we found that sera of septic mice following cecal ligation and puncture (CLP) had much higher chemotactic activities on neutrophils than those of sham animals. Compared with wild-type (WT) mice, FB −/− mice had significantly attenuated serum chemotactic activity, under both nonseptic and septic conditions. Moreover, sera with the activated AP by zymosan and cobra venom factor (CVF) in vitro induced a significant increase in neutrophil migration compared with sera without the AP activation. Complement activation generates complement cleavage fragment such as Ba, C3a, and C5a. To delineate the contribution of these downstream effectors, we incubated AP-active sera (AP activated by zymosan/CVF) or sera from sham and septic mice with anti-C5a or mAb1379 (anti-Ba) neutralizing antibody. We found that anti-C5a, but not mAb1379, markedly attenuated the neutrophil chemotactic effect of the AP-activated sera and that of septic sera. Taking together, these data suggest that the complement AP activation during bacterial sepsis plays a pivotal role in promoting blood chemotactic activity through a C5a-dependent mechanism.